1991
DOI: 10.1038/bjc.1991.390
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor in lung malignancies. Comparison between cancer and normal tissue

Abstract: Summary Epidermal growth factor receptors (EGFr) were measured using a radioligand binding assay, in membrane preparations from 51 human non-small cell lung cancers and in normal tissue of the same patients.The binding characteristics of EGFr were similar in tumour and normal lung membranes (range of dissociation constant of high affinity sites: 0.1-0.6 nM). However, the concentrations in tumours (median, 16.4 fmol mgI of protein; range, 1.5-176) were significantly higher than in normal tissues (median, 7.4 fm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The difference between the mean concentration of EGFR in membrane fractions of tumor and normal tissue were insignificant (76.0+19.1 and 57.7_+10.1 fmol/ml protein, respectively). This finding agrees with previously reported hyperexpression of EGFR in tumors in comparison with normal lung [9,13,14]. However, a tendency (X2=3.27, p=0.07) toward a more frequent expression of EGFR in tumor tissues (75%) in comparison with normal tissue (68%) was revealed.…”
Section: Resultssupporting
confidence: 93%
“…The difference between the mean concentration of EGFR in membrane fractions of tumor and normal tissue were insignificant (76.0+19.1 and 57.7_+10.1 fmol/ml protein, respectively). This finding agrees with previously reported hyperexpression of EGFR in tumors in comparison with normal lung [9,13,14]. However, a tendency (X2=3.27, p=0.07) toward a more frequent expression of EGFR in tumor tissues (75%) in comparison with normal tissue (68%) was revealed.…”
Section: Resultssupporting
confidence: 93%
“…Dittadi et al used a radioligand binding assay on 51 NSCLC and showed, like us, a significantly higher concentration of EGFr in tumours compared to normal lung (Dittadi et al, 1991). They found no relationship between histology or stage and receptor concentration.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is expressed in the skin, liver, digestive tract and reproductive organs (36)(37)(38). The distributions of EGFR in various tissues can also be found at the human protein atlas (http://www.proteinatlas.org/).…”
Section: (A) Egfr Primary Tumor (3+) (B) Egfr Lymph Node Metastamentioning
confidence: 99%